Disaggregated Helicobacter pylori Biofilm Impairs Bactericidal Activity and Bacterial Phagocytosis by Human Neutrophils - Clara Lourdes Tovar-Robles; Yolanda Romo-Lozano; Daniel Cervantes-García; Rodolfo González-Segovia (Microbiology Research)
Helicobacter pylori (H. pylori), a prevalent human pathogen affecting nearly half the global population, is a major contributor to chronic gastritis, peptic ulcer, and gastric cancer. H. pylori develops biofilms (BFs) allowing bacteria to evade the immune response. Differences in composition between planktonic and biofilm cells influence the host’s immune response, yet the specific biofilm components modulating this response remain uncharacterized. Considering the above, this study evaluated the effect of in vitro-generated H. pylori BF on the antibacterial activity of neutrophils. This work utilized sonication to obtain disaggregated H. pylori BF (d-BF-Hp) to challenge human neutrophils, assessing their bactericidal and phagocytic activity against Staphylococcus aureus. S. aureus survival in the presence of neutrophils was enhanced by 10 μg/mL of d-BF-Hp’s protein. Conversely, S. aureus survival was significantly lower at 30 µg/mL compared to 10 µg/mL d-BF-Hp. Furthermore, 10 and 30 µg/mL of d-BF-Hp significantly reduced the neutrophil phagocytosis rate. Our findings suggest that d-BF-Hp components diminish neutrophil bactericidal activity, although this effect was not observed at higher d-BF-Hp concentrations. Increased d-BF-Hp concentrations proportionally reduced neutrophil phagocytic capacity. Future work should explore the mechanisms underlying the alteration of neutrophil microbicidal properties.